Complementary and Integrative Health Services in a Low-resource Community: a Retrospective Examination - (:unkn) unknown (My University, 2017)
ABSTRACT COMPLEMENTARY AND INTEGRATIVE HEALTH SERVICES IN A LOW-RESOURCE COMMUNITY: A RETROSPECTIVE EXAMINATION by Barbara M. Wesson The University of Wisconsin – Milwaukee, 2017 Under the Supervision of Professor Ron Cisler Study Background and Significance: Complementary and Integrative Health (CIH) continues to be widely utilized despite a lack of consensus regarding its efficacy. Since 2001, CORE El Centro (CEC) has been providing acupuncture, massage, reiki, and mindful movement classes, charging sliding scale fees in a low-resource, primarily Latino community; underrepresented in the CIH literature. Purpose: This study examined the association between CIH use (time and treatment), subjective well-being assessments, biometrics records, as well as the association of reduced fees on service utilization in a low-resource community. Methods: CEC provided information from 1278 de-identified client records spanning 24-months. Within those records, 622 clients had received four or more treatments. Data preparation included reduction of 29 dependent variables (the subjective well-being questions) into four Health Factors (cognitive, emotional, physical, and medical). Additional dependent variables included total number of health conditions reported and a General Health response. Independent variables included length of engagement and types and frequencies of services used. Associations were examined between level of payment for services, utilization, and health conditions. Spaghetti and scatter plots were used to explore trends of change across time. Paired sample tests assessed significant change between assessments. Results: General Health, Total Health Conditions, and three Health Factor scores improved over time. Biometric health status indicators did not change significantly, but were with normal range at the first recording. Clients receiving four or more treatments averaged 12 treatments over eight months. A significant inverse association existed between payment level and Health Conditions. Clients in the low payment level group that reported more Health Conditions used more services and clients in the highest payment level group that reported fewer Health Conditions used more services. Conclusion: The cost of CIH may be one of the primary barriers to utilization, because when fees for service are scaled to income a low-resource community will use CIH. The Latino community demonstrated they will use CIH. Increased use by individuals with chronic conditions was supported. Subjective health and well-being improved. This study supports the rich history of research asserting the complexity in the study of CIH in a community-based center. Future Directions: There is a need to create community based research to further understand CIH as well as the socioeconomic and cultural influence inherent in CIH utilization. The next step is to create deeper partnerships between Universities and health care systems toward developing systems for tracking, monitoring, and analysis that are effective for both research and practitioners of CIH.
Keywords: Community-based Research; Complementary and Integrative Health; Latino; Low-resource; Reduced Fees; Whole Systems Research